Mobile-based assessment: Investigating the factors that influence behavioral intention to use. (June 2017) - Nikou, Stavros A.; Economides, Anastasios A.
Abstract: Acceptance and intention to use mobile learning is a topic of growing interest in the field of education. Although there is a considerable amount of studies investigating mobile learning acceptance, little research exists that investigates the driving factors that influence students' intention to use mobile technologies for assessment purposes. The aim of this study is to provide empirical evidence on the acceptance of Mobile-Based Assessment (MBA), the assessment delivered through mobile devices and technologies. The proposed model, Mobile-Based Assessment Acceptance Model (MBAAM) is based on the Technology Acceptance Model (TAM). MBAAM extends TAM in the context of MBA by adding to the Perceived Ease of Use and Perceived Usefulness, the constructs of Facilitating Conditions, Social Influence, Mobile Device Anxiety, Personal Innovativeness, Mobile-Self-Efficacy, Perceived Trust, Content, Cognitive Feedback, User Interface and Perceived Ubiquity Value and investigates their impact on the Behavioral Intention to Use MBA. 145 students from a European senior-level secondary school experienced a series of mobile-based assessments for a three-week period. Structured equation modeling was used to analyze quantitative survey data. According to the results, MBAAM explains and predicts approximately 47% of the variance of Behavioral Intention to Use Mobile-Based Assessment. The study provides a better understanding towards developing mobile-based assessments that support learners, enhance learning experience and promote learning, taking advantage of the distinguished features that mobile devices may offer. Implications are discussed within the wider context of mobile learning acceptance research. Highlights: The study investigates factors influencing students' adoption of mobile-based assessment. The study introduces Mobile-Based Assessment Acceptance Model (MBAAM). MBAAM explains about 47% of the total variance in Behavioral Intention to Use.